Gamma, charged particle and neutron radiation shielding capacities of ternary composites having polyester/barite/tungsten boride - POLAT, HAMZA (My University, 2023)
The presented work investigates the photon, charged particle and neutron radiation shielding performances of polyester-based composites filled with barite and/or tungsten boride by using experimental, theoretical, and Monte Carlo simulation techniques. The amount of barite/tungsten boride varying from 0 wt% to 50 wt% in the material and polyester resin were exploited as filler and base materials, respectively. Experimental evaluation of BaWB composites has been performed with help of an HPGe detector based gamma spectrometer as well as 22Na, 133Ba, 137Cs and 60Co radioactive point sources with energies in the range of 276.4–1332.5 keV. The experimental data were compared to those theoretically calculated in WinXCOM as well as Monte Carlo (MC) simulations, i.e., MCNP6, GEANT4 and FLUKA codes. The obtained mass attenuation coefficients for the produced composites were in good agreement with the results of MC simulations and WinXCOM software. Comparing to the other polymer composite samples, the sample with the maximum tungsten boride weight percentage has the best radiation shielding property because of having the highest attenuation coefficients and lowest absorption thicknesses.
Keywords: Fizik; Nükleer Fizik; Temel Bilimler; Physics; Nuclear physics; Natural Sciences; Temel Bilimler (SCI); NÜKLEER BİLİMİ VE TEKNOLOJİSİ; Natural Sciences (SCI); PHYSICS; NUCLEAR SCIENCE & TECHNOLOGY; Radyasyon; Fizik Bilimleri; Radiation; Physical Sciences; Barit; Gamma-ray spectrometer; Monte-Carlo codes; Shielding efficiency; Tungsten boride